Globalization and indigenisation: Repositioning social work within a changing environment - Weyers, ML (Social Work/Maatskaplike Werk, 2001)
ENTER SIR ISAAC NEWTON According to Newton’s first law of motion, " . .. any object in a state of rest or of uniform linear motion tends to remain in such a state unless acted upon by an unbalanced external force ... " His third law, which is also known as the principle of action and reaction, states that " ... every action ( or force) gives rise to a reaction ( or opposing force) of equal strength but opposite direction" (Settles, 1996). In other words, every object that exerts a force on another object is always acted upon by a reaction force. The extent to which the fundamental natural laws of classical mechanics is applicable to the human condition and social work has been open to questioning since general systems theory married the ecological approach in the 1980s, and even subject to ridicule since the arrival of the newest kid on the block: chaos theory (alias non-equilibrium/self-organisation/complex systems theory) (Hudson, 2000:215,219). However, the temptation to draw an analogy between it and globalisation is overwhelming. GLOBALISATION Although globalisation has been an "object" in accelerating motion for decades, it only burst into our collective consciousness with the dawning of the Internet age and the arrival of the "global village". Then it became a hotly debated issue not only on the international economic and politicai stage, but in social work as well. The result was the adoption of "Social Work and Globalisation" as the theme for the joint conference of the International Association of Schools of Social Work (IASSW) and International Federation of Social Workers (IFSW) held in Canada in 2000. In spite of the conference, what is meant by "globalisation" is still (as in the case of beauty) somewhat in the eye .of the beholder. Therefore the following, somewhat esoteric definition will have to suffice for this argument’s sake: "Globalisation is the process of worldwide unification of economic, social, political and cultural orientation through a borderless society ... " (Rowe et al., 2000:70).